A Germylene Stabilized by Homoconjugation. Issue 51 (17th November 2016) - Dong, Zhaowen; Reinhold, Crispin R. W.; Schmidtmann, Marc; Müller, Thomas
Abstract: The synthesis of a bicyclic germylene from the reaction of a germole dianion with hafnocene dichloride is reported. This germylene is stabilized by a homoconjugative interaction of the dicoordinated germanium atom with a remote C=C double bond. First reactivity studies revealed its nucleophilic character and resulted in the synthesis of bimetallic hafnium/iron and hafnium/tungsten complexes with a germylene group linker. Abstract : A germane approach to stabilization : A germylene stabilized by homoconjugation is described. The structural parameters and a theoretical analysis of the bonding situation revealed a homoconjugative interaction between the C=C bond and the empty Ge 4p orbital. Reactivity studies confirmed its nucleophilic character, and bimetallic hafnium/iron and hafnium/tungsten complexes were synthesized.